Modal Choice Analysis of Electric Railway Train and Private Vehicle for Travelers in Mangga Dua With Stated Preference Method - Andri Irfan Rifai; Shahar Banu; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
Transportation activity is a vital need for urban economic development. Mangga Dua, as a shopping center area and many other commercial points, has been supported by various modes of public transportation, one of which is the Electric Rail Train (KRL). The Bekasi area and its surroundings are a supporter of the transportation and agglomeration of Jakarta. Every day, many Bekasi people use the KRL for mobility activities to various areas covered by the KRL, including Mangga Dua. Even so, many private vehicle users still depend on road infrastructure which causes traffic congestion problems for Jakarta – Bekasi mobility. However, the fact that the Cikarang - Kampung Bandan KRL route is always busy indicates that KRL is still a solution for Bekasi - Jakarta transportation problem that many people choose. This research is intended to determine what factors influence the choice of KRL mode and what factors influence the choice of that mode. The method used is stated preference by collecting primary data using questionnaires from respondents who commute using Cikarang – Kampung Bandan Line. Data processing and analysis were carried out with the help of SPSS software version 16.0. The data processing and analysis results show that the factors influencing the choice of KRL mode are cost-effectiveness, safety, and convenience. Congestion and ease of access are the most influential factors afterward, and the effectiveness of travel time is the last order factor out of 5 factors in the most influential hypothesis. With the result that 71% of respondents chose KRL over motorbikes, it was concluded that KRL as a rail-based mode is a solution to the Jakarta - Bekasi transportation problem.